Perbaikan Manajemen Pergudangan Plant B di PT XYZ - Erens Feliciano Kusuma (Jurnal Titra, 2017)
PT. XYZ wants a good warehouse management because of the large number of motorcycle tires produced. Warehouse plant B PT XYZ is a storage for OEM tires, which is the highest quality tires. The problems that exist in warehouse plant B are FIFO (First In First Out) system, tire defect when stored, and lack of rack placement. The proposed improvements are layout, check sheet, control board, and rack for plant B. Goals from this thesis are increasing warehouse management system plant B to meet customer requirements.